2012
DOI: 10.2298/jsc100924152s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of 4-thiazolidinone derivatives of phenothiazine

Abstract: A new series of N-[3-(10H-phenothiazinyl)-propyl]-2-(substituted phenyl)-4-oxo-5-( substituted benzylidene)-1,3-thiazolidine-carboxamide, 5(as) have been synthesized. The cycloaddition reaction of thioglycolic acid with N-[3-(10H-phenothiazinyl)-propyl]-N’-[(substituted phenyl)-methylidene]- urea, 3(a-s) in the presence of anhydrous ZnCl2 afforded new heterocyclic compounds N-[3-(10H-phenothiazinyl)-propyl]-2-(substituted phenyl)-4-oxo- 1,3-thiazolidine-carboxamide, 4(a-s). The later product on treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Alconea Palafox et al [14] had given a complete vibrational analysis of the Fourier transform (FT) infrared (IR) and FT-Raman spectra of both phenothiazine (PTZ) and N-methylphenothiazine molecules using ab initio method as well as quantum chemical calculations. Sharma et al [15] found the better biological activity of 4-thiazolidinone derivatives of phenothiazine. Dixit et al [2] had synthesized some 10H-phenothiazine sulphone derivatives and characterized them with selected bands of IR and 1H NMR spectroscopic methods.…”
Section: Introductionmentioning
confidence: 98%
“…Alconea Palafox et al [14] had given a complete vibrational analysis of the Fourier transform (FT) infrared (IR) and FT-Raman spectra of both phenothiazine (PTZ) and N-methylphenothiazine molecules using ab initio method as well as quantum chemical calculations. Sharma et al [15] found the better biological activity of 4-thiazolidinone derivatives of phenothiazine. Dixit et al [2] had synthesized some 10H-phenothiazine sulphone derivatives and characterized them with selected bands of IR and 1H NMR spectroscopic methods.…”
Section: Introductionmentioning
confidence: 98%
“…The broad and potent activity of thiadiazole and their derivatives has established them as pharmacologically significant scaffolds. Thiazolidinones scaffolds are reviewed extensively in literature for its vibrant activities such as antibacterial (Kandapalli V. G. et al 2010), antifungal (Sharma R. et al 2012), antioxidant (Parmeshwaran M. et al 2009), cytotoxic (Jubie S. et al 2009), antiinflammatory (Goel B. et al 1999), anticonvulsant (Chaudhary M. et al 1976), anti-HIV (Rawal R. et al 2005), anti-tubercular (Aamer S. et al 2007), antiviral activities (Murugesan S. et al 2012) and DNA Binding Agent (War J. et al 2017). The incorporation of 4-oxothiazolidine and 5-arylidene moieties in 2amino-5-ethyl-1,3,4-thiadiazole frame work has been found to enhance the activity.…”
Section: Introductionmentioning
confidence: 99%
“…Antihistamines, diuretics, analgesics, neurolepitcs, antileukemic, antimutagenic, antileishmanial etc. are some of their main potential applications [2][3][4][5][6][7] of the drugs that containing phenothiozenes. Pallafox et.…”
Section: Introductionmentioning
confidence: 99%
“…al. [7] reported various remarkable biological activities of thiazolidines. Previously, we have revealed vibrational analysis of 10-Acetyl-10H-phenothiazine5-oxide [APTZ] using quantum chemical calculations [8].…”
Section: Introductionmentioning
confidence: 99%